Stability analysis of a сlosed non-linear system “FC-BM” of the electric drive of an electric vehicle - Z. Yerlan, Amangaliyev; I. Yuri, Shadkhin (Bulletin of Electrical Engineering and Informatics, 2024)
The article presents the analysis and stability program of the closed non-linear system frequency converter-brushless motor “(FC-BM)”, which differs significantly from the analysis of linear systems. First of all, this is because the stability property of a nonlinear system depends on the initial conditions and external influences: for some input signals, the system will be stable, while for others it becomes unstable. Consequently, the stability criteria developed in the linear theory cannot be applied to their analysis. The stability of a non-linear automatic control system means that small changes in the input signal or disturbances, initial conditions, or plant parameters will not take the output variable beyond a sufficiently small neighborhood of the equilibrium point or limit cycle. Since several equilibrium positions can exist for a non-linear system, stability should be analyzed in the vicinity of each of them. This complicates the task of research.